Sustainable Development Goals – Humanising science beyond the lab - Julia Cassarotti (BioScientist: The Salford Biomedicine Society Magazine, 2024)
The United Nations (UN) has developed 17 objectives to improve education, health and sanitation, poverty, hunger, etc. These objectives are called Sustainable Development Goals (SDGs). This article mainly focused on SDG 3, which promotes ideal health and well-being, where scientific contribution has been essential to its development. Nevertheless, barriers to poverty seen in Sub-Saharan regions have limited further advancements, requiring social protection programme investment through the government. Expansion of HIV treatments, such as Cabenuva, has reduced AIDS-related deaths by 50%, although eradication of social discrimination is essential to surpass the AIDS-related stigma present since the 1980s. An estimated 80% of women will be content with their reproductive health by 2030, for instance, due to the development of the HPV vaccine, which prevents cervical cancer. A drastic decline in vaccination is still observed, which calls for more efficient vaccination incentives. Lastly, the article focused on goal 12, highlighting the importance of replacing medical plastic with biodegradable materials such as starch to ensure a more sustainable and eco-friendly environment. In the next six years, economic and socio-protective regulations will be needed as a starting point for the SDG targets to be possible to reach by 2030.